2014
DOI: 10.1016/j.bbmt.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

CD34 Selected Cells for the Treatment of Poor Graft Function after Allogeneic Stem Cell Transplantation

Abstract: Poor graft function (PGF) is characterized by pancytopenia and a hypoplastic marrow, with complete donor chimerism, usually without severe graft-versus-host disease (GVHD). We report 41 patients with PGF, treated with granulocyte colony-stimulating factor-mobilized CD34 selected cells, at a median interval from transplant of 140 days, without conditioning and without GVHD prophylaxis. Donors were HLA matched siblings (n = 12), unrelated donors (n = 18), or mismatched family members (n = 11). The median number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 11 publications
3
60
0
4
Order By: Relevance
“…It is important to note that the SCB created from cryopreserved products yielded the lowest median CD34 + cell doses; the median CD34 + yield was 61.5% (range 42–95%), 68.5% (range 37–83%), and 28% (range 10–34%) for G-CSF plus plerixafor, G-CSF only, and cryopreserved products, respectively. Other studies have reported no correlation between CD34 + cell dose and PGF response to SCB [16, 17]. …”
Section: Discussionmentioning
confidence: 92%
“…It is important to note that the SCB created from cryopreserved products yielded the lowest median CD34 + cell doses; the median CD34 + yield was 61.5% (range 42–95%), 68.5% (range 37–83%), and 28% (range 10–34%) for G-CSF plus plerixafor, G-CSF only, and cryopreserved products, respectively. Other studies have reported no correlation between CD34 + cell dose and PGF response to SCB [16, 17]. …”
Section: Discussionmentioning
confidence: 92%
“…This is a question needed to answer in our further study. Some recent reports [20,21] suggest that patients with idiopathic myelofibrosis might have higher incidence of PGF than patients with other underlying disease. However, incidence and pathogenesis were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Although some patients received a second infusion of donor cells or even second transplantation, the efficacy was very poor. Some recent studies have shown promising results from treating with a booster of CD34+ cells [20][21][22]; however, we should note that most patients who received the boosted cell infusion had secondary PGF, and we have already demonstrated that primary PGF has significantly worse prognosis than secondary PGF [4]. New therapeutic options are warranted to manage primary PGF on the basis of better understanding of primary PGF.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Askaa et al, 8 Klyuchnikov et al 9 and Stasia et al 10 reported promising results in treating PGF patients with a CD34 + -selected stem cell boost without further conditioning. However, it should be noted that most patients who received the boosted CD34 + cell infusion had late PGF.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the available treatment options for PGF are limited and include the administration of hematopoietic growth factors, a second allo-HSCT, or a CD34 + -selected stem cell boost, among others. 1,[8][9][10] Therefore, obtaining a better understanding of the pathophysiology of PGF promises to guide more effective therapeutic approaches and eventually improve survival.…”
Section: Introductionmentioning
confidence: 99%